Communication Strategies of Counselors in Out Patient Rehabilitation Programs at the Primary Clinic of the National Narcotics Agency, Sumatera Utara Province - Sanra, Arie; Lubis, Lusiana Andriani; Nurbaini, Nurbaini (Formosa Journal of Applied Sciences, 2024)
The communication strategies employed by counselors play a pivotal role in outpatient rehabilitation programs. Effective communication is crucial for building trust, understanding clients, and achieving successful outcomes. The research method employed in this study is the qualitative research method, which is characterized by its logical and systematic approach to investigating or observing phenomena. Counselors play a crucial role in establishing a foundation of trust and understanding with their clients. This, in turn, positively influences the rehabilitation process. The incorporation of various communication techniques and mediums helps tailor messages to each client's specific needs and preferences. In conclusion, effective communication is at the heart of successful outpatient rehabilitation programs. Counselors must utilize a range of strategies to understand their clients, deliver tailored messages, and engage through various communication mediums.